LISTA RECENZENTÓW ROCZNIKA 2016 - SP, Redakcja (Studia Psychologica: Theoria et praxis, 2016)
Małgorzata Basińska Sylwia Bedyńska Agata Błachnio Jerzy Bobryk Danuta Borecka-Biernat Jerzy Brzeziński Barbara Ciżkowicz Bartłomiej Dobroczyński Marcin Domurat Barbara Gawda Ryszard Gryglewski Jan Hertrich-Woleński Zygfryd Juczyński Barbara Kałdon Dariusz Krok Krzysztof Krzyżewski Monika Książek Maria Ledzińska Hanna Liberska Wiesława Limont Eugenia Mandal Jarosław Matysiak Barbara Mróz Nina Ogińska-Bulik Andrzej Pankalla Krzysztof Rutkowski Krystyna Skarżyńska Paweł Smółka Ryszard Stachowski Małgorzata Stawiak-Ososińska Barbara Szmigielska-Siuta Aleksandra Tokarz Zenon Uchnast Jan Wnęk